Smart tourism destination governance : technology and design-based approach - Gajdošík, Tomáš, 1988- (Routledge focus on tourism and hospitality, 2022)
Drawing upon empirical research and critical literature review, Smart Tourism Destination Governance: Technology and Design-Based Approach provides a comprehensive overview and analysis of smart tourism destination governance and its related challenges. Building on the author's extensive research background in tourism destinations and information technologies, the book provides a quantitative approach to the phenomenon, using cluster and network analysis. It uses design thinking to provide solutions on how to overcome the challenges faced within the context of tourism destination governance, with a detailed discussion of the contribution of the smart approach to overcoming such challenges. The book is presented in three parts as follows: Part 1: The Need for a New Form of Tourism Destination GovernancePart 2: The Contribution of Smart Approach to Overcoming the Challenges of Tourism Destination GovernancePart 3: Designing Smart Tourism Destination Governance Towards Sustainability, Competitiveness and Resilience This work will be of great interest to both tourism scholars and decision-makers within the field of tourism, aiming to provide a detailed overview of and broaden the reader's horizons in regards to the possibilities of the smart approach to tourism destination governance.